Effective Justice - Crisp, Roger (Journal of moral philosophy, 2020)
Effective Altruism is a social movement which encourages people to do as much good as they can when helping others, given limited money, time, effort, and other resources. This paper first identifies a minimal philosophical view that underpins this movement, and then argues that there is an analogous minimal philosophical view which might underpin Effective Justice, a possible social movement that would encourage promoting justice most effectively, given limited resources. The latter minimal view reflects an insight about justice, and our non-diminishing moral reason to promote more of it, that surprisingly has gone largely unnoticed and undiscussed. The Effective Altruism movement has led many to reconsider how best to help others, but relatively little attention has been paid to the differences in degrees of cost-effectiveness of activities designed to decrease injustice. This paper therefore not only furthers philosophical understanding of justice, but has potentially major practical implications.